Flora of Singapore: Checklist and bibliography - Lindsay, S.; Middleton, D.J.; Ho, B.C.; Chong, K.Y.; Wong, Sin Yeng (2022)
A checklist of all species of bryophytes, lycophytes, ferns, gymnosperms and angiosperms that are found in the wild (native, naturalised and casual) in Singapore is presented. We have attempted to account for all names of species and infraspecific taxa that have ever been recorded for Singapore, along with the pertinent publications that reported each of these names. For each currently accepted name, the synonyms of relevance for Singapore are included. The native or non-native status for all taxa is given, along with the most recent national conservation assessment applied to each native taxon. If we were aware that the most recent assessment required an update, the taxon is newly assessed here. The checklist includes 2654 native taxa, 479 naturalised/casual taxa and 101 cryptogenic taxa.